2023
DOI: 10.1038/s41598-023-27879-8
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function three to five months after hospital discharge for COVID-19: a single centre cohort study

Abstract: Some COVID-19 survivors suffer from persistent pulmonary function impairment, but the extent and associated factors are unclear. This study aimed to characterize pulmonary function impairment three to five months after hospital discharge and the association with disease severity. Survivors of COVID-19 after hospitalization to the VieCuri Medical Centre between February and December 2020 were invited for follow-up, three to five months after discharge. Dynamic and static lung volumes, respiratory muscle strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 38 publications
2
6
1
Order By: Relevance
“…44,47 Corticosteroid treatment was linked to better lung function recovery, 33,47 while this was not observed with other treatment modalities. 39 Overall, our study ndings are consistent with most of other studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…44,47 Corticosteroid treatment was linked to better lung function recovery, 33,47 while this was not observed with other treatment modalities. 39 Overall, our study ndings are consistent with most of other studies.…”
Section: Discussionsupporting
confidence: 92%
“…China have respectively reported signi cantly lower dynamic lung volumes in patients with more severe illness, 31,38 while another study in the Netherlands found only FVC to be signi cantly lower in such cases. 39 Additional studies have shown that for individuals post-COVID-19, spirometry indices were not signi cantly different from the healthy population, 40 those with other viral upper respiratory tract infections, 41 or the same cohort of patients one year before the infection. 42 A review by Thomas et al further concluded that spirometry indices are often well-preserved in COVID-19, without being signi cantly affected by illness severity.…”
Section: Discussionmentioning
confidence: 97%
“…Krueger et al assessed lung function in 257 patients presenting mean COVID-19 duration of 112 days and observed reduced FEP and FIP in 24% and 9% of patients, respectively. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have examined the relationship between COVID-19 and respiratory complications. However, previous research encompassed countries such as Brazil ( n = 88) 10 , Palestine ( n = 705) 11 , and Netherlands ( n = 257) 12 , with small cohorts and without a general population group as controls or influenza cohort as an external comparator. In addition, previous studies did not consider the subtypes of specific respiratory diseases, vaccinations, and severity of COVID-19 on the association between respiratory outcomes and SARS-CoV-2 infections 13 .…”
Section: Discussionmentioning
confidence: 99%